2008
DOI: 10.1007/s11692-008-9032-9
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Instability—Sexual Selection Hypothesis: A General Evaluation and Case Study

Abstract: Developmental instability results from small, random perturbations to developmental processes of individual traits. Phenotypic outcomes of developmental instability include fluctuating asymmetry (FA, subtle deviations from perfect bilateral symmetry) and phenodeviance (minor morphological abnormalities). A great deal of research over the past 18 years has focused on the role of developmental instability in sexual selection. A driving force behind this research has been the developmental instabilitysexual selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 232 publications
(339 reference statements)
0
35
0
Order By: Relevance
“…Whereas several studies have reported negative FA-size correlations in secondary sexual traits [20,22,23], others have not [24][25][26][27]. Such inconsistent findings have brought critical attention to the theoretical foundation of the prediction and to its validity [28][29][30], and question the generality of the DI-sexual selection hypothesis [13,31].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas several studies have reported negative FA-size correlations in secondary sexual traits [20,22,23], others have not [24][25][26][27]. Such inconsistent findings have brought critical attention to the theoretical foundation of the prediction and to its validity [28][29][30], and question the generality of the DI-sexual selection hypothesis [13,31].…”
Section: Introductionmentioning
confidence: 99%
“…The sex comb is composed of heavily melanized teeth internally made up of structural protein filaments (Tilney et al, 2000). The comb size (as tooth number) may be particularly sensitive to temperature stress because high temperatures can induce the production of protective proteins (Feder & Hofmann, 1999), which potentially can channel resources away from the sex comb during development (Polak, 2008). In D. bipectinata, the teeth of the two major segments, C1 (3-8 teeth) and C2 (5-12 teeth), are arranged in two rows on the first tarsal segments of the forelegs (a third, smaller, set of 0-3 teeth occur on the second tarsal segment of each leg, which is not considered here).…”
Section: Introductionmentioning
confidence: 99%
“…A multivariate analysis of selection in a population of D. bipectinata demonstrated that a relatively large C2 and male body size were independently associated with increased mating probability in the field, and hence that these traits are under significant positive sexual selection (Polak et al, 2004;Polak, 2008). By contrast, mating probability was statistically independent of variation in C1 and sternopleural bristle number (Polak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Females of many Drosophila species mate preferentially with males with particular phenotypes, like body size, eye colour, courtship song parameters, physiological ability, behavioural patterns (ETGES & NOOR 2002 and references herein;PARTRIDGE 1994), sometimes symmetry in "ordinary" morphological characters and/or secondary sexual traits (SANTOS 2001, POLAK 2008 or, in some species, quality and quantity of a nuptial gift may be the target of sexual selection (STEELE 1986).…”
Section: Introductionmentioning
confidence: 99%